Pharmaceutical Compounding in Veterinary Medicine: Suspension of Itraconazole - Gema J. Cabañero-Resta; Bárbara Sánchez-Dengra; Alejandro Ruiz-Picazo; Marival Bermejo; Virginia Merino; Isabel Gonzalez-Alvarez; Marta Gonzalez-Alvarez (MDPI AG, 2024)
Itraconazole is a drug used in veterinary medicine for the treatment of different varieties of dermatophytosis at doses between 3-5 mg/kg/day in cats. Nevertheless, in Spain, it is only available in the market as a 52 mL suspension at 10 mg/mL. The lack of alternative formulations, which provide sufficient formulation to cover the treatment of large animals or allow the treatment of a group of them, can be overcome with compounding. For this purpose, it has to be considered that itraconazole is a weak base, class II compound, according to the Biopharmaceutics Classification System, that can precipitate when reaching the duodenum. The aim of this work is to develop alternative oral formulations of itraconazole for the treatment of dermatophytosis. Several oral compounds of itraconazole were prepared and compared, in terms of dissolution rate, permeability, and stability, in order to provide alternatives to the medicine commercialized. The most promising formulation contained hydroxypropyl methylcellulose and β-cyclodextrin. This combination of excipients was capable of dissolving the same concentration as the reference product and delaying the precipitation of itraconazole upon leaving the stomach. Moreover, the intestinal permeability of itraconazole was increased more than two-fold.